121k views
2 votes
Solve 4- 3x = 6 - 5x
X =

User Greta
by
4.8k points

2 Answers

5 votes

Answer:

Explanation:

4 - 3 x = 6 - 5 xx


-3x+4=6-5xx^(2)

x = 1

x = -
\frac {2}{5}

User Patrick Mineault
by
5.2k points
1 vote

Answer:

x=1

Explanation:

sense x's are on both sides you need to bring one of them over, add 3x to both sides to get 4=6-2x , then subtract 6 from each side to get -2=-2x , then to get x by itself divide both sides by -2 to get 1=x

User Manos
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.